Electroencephalography and epilepsy - Schomer, Donald (Henry Stewart Talks, 2011)
Fundamentals of recording EEG, Hyperventilation, Intermittent photic stimulation (IPS), Routine activating techniques, Special electrodes, Telemetry-based recording, EEG recording patterns of seizures, epilepsy, syndromes and disorders, Partial seizures, MELAS, Psychomotor variant, Mu rhythm, Small sharp spikes, Wickets, Midline theta, SREDA, Cardiac rhythm changes -SaO2 abnormalities
Reviewed at 2020/07/19